Analysis of the effect of current on tensile strength of aisi 1050 material in the SMAW welding process - Aris Mauliza; Usman Usman; Saifuddin Saifuddin (Politeknik Negeri Lhokseumawe, 2022)
Shield Metal Arc Welding (SMAW) which is also called Electric Arc Welding is a welding process that uses heat to melt the base material or base metal and electrodes (fill material). Meanwhile, at the processing stage, the appropriate current strength will be selected to the working position. The purpose of this study was to determine the effect of welding current on the mechanical strength of AISI 1050 medium carbon steel. The currents used were 100 A, 125 A and 150 A. After doing research, SMAW welding on AISI 1050 medium carbon steel with variations in current affects the value tensile strength, stress and strain that occur after welding. As the results obtained are for welding currents with a current of 150 A having the highest tensile strength of 74.36 kgf/mm2, while for a current of 100 A having a tensile strength of 72.94 kgf/mm2, while the lowest value is at a current of 125 A which has a tensile strength of 51.45 kgf/mm2. , while the strain that occurs at a current of 100 A is 10.13%, while at a current of 125 A the strain that occurs is 5.27%, and at a current of 150 A that is 9.92%